Juegos lúdicos y lenguaje oral en niños de 4 a 5 años, Escuela de Educación Básica Vicente Bastidas Reinoso, ciudad de Loja, periodo 2023-2024 - Yaguana Abad, Yuri Lisbeth (2024)
Oral language represents one of the primordial capacities of human beings to facilitate communication, playing a crucial role in the cognitive, emotional, affective, and social development of the individual; it is essential that during childhood language is stimulated to allow children to communicate effectively with others, express their needs, emotions and thoughts, expressing their ability to solve problems and understand the world around them, to establish relationships with their peers, all this contributes to have a comprehensive development, with the main objective of determining how playful games affect the development of oral language in children aged 4 to 5 years, Vicente Bastidas Reinoso School, city of Loja, period 2023-2024. This study was carried out using a quantitative and qualitative approach, quasi-experimental design, descriptive scope, using deductive and inductive methods. The tool used as an instrument to obtain the results was the Plon-R test. After the intervention, it was observed that the percentage of children in a normal state increased from 18% to 54%, which resulted in a significant increase in the normal level. Based on the results, the researcher concludes that playful games represent an extremely valuable educational resource that positively influences oral language development. Through these games, children have the opportunity to express themselves freely, enjoy, learn, and collaborate as a team. Thus, stimulating their creativity and imagination while favoring the teaching and learning process in all areas in which they develop. Key words: recreational activities, teachers, oral expression, infants, high school.